08.34 Ra synovial recombinant monoclonal antibodies from single b cells target citrullinated calreticulin. (1st March 2017) - Corsiero, Elisa; Jagemann, Lucas; Prediletto, Edoardo; Pitzalis, Costantino; Bombardieri, Michele
Abstract : Background: Fibroblast-like synoviocytes (FLS) play a crucial role in the pathogenesis of rheumatoid arthritis (RA) directly contributing to local cartilage destruction and synovial inflammation. 1 Autophagy, a mechanism whereby damaged proteins are removed from the cells, has been implicated in the pathogenesis of RA by activating the citrullination process in RA-FLS. 2 The protein expression pattern of FLS has been also characterised with the identification of >200 proteins which have been involved in the normal or pathological FLS function. 3 Among all the proteins identified in the RA-FLS, calreticulin (CRT) has been implicated in the pathogenesis of RA. 4, 5 In particular, citrullinated-(cit)-CRT has been shown to better recognise the RA 'share epitope' HLA domain compared to native CRT. 4 Therefore, here we tested the immunoreactivity of RA synovial recombinant monoclonal antibodies (RA-syn-rmAbs) towards RA-FLS and towards cit-CRT. Materials and methods: 82 RA-syn-rmAbs were generated from single CD19+B cells FACS-sorted from fresh synovial cell suspensions following IgVH +VL genes cloning (6). RA-syn-rmAbs were tested by means of i) cell-based immunofluorescence assays with FLS of RA patients and controls (osteoarthritis (OA)/healthy donors (HD)-FLS and dermal fibroblast (DF)) and ii) immunoenzymatic tests using native/cit-CRT. Control rmAbs were also used (Sjögren's syndrome/HD-IgG rmAbs). Results: Immunofluoresce on RA-FLS demonstrated reactivity of 21% of RA-syn-rmAbs (14/67 mAbs) towards cytoplasmic/nuclear components of FLS. This reactivity was not exclusively directed against RA-FLS since it was also observed for OA/HD-FLS and DF. When tested in ELISA for native vs cit-CRT, 50% (7/14 mAbs) of the FLS+ RA clones showed to be reactive towards CRT. Interestingly, 4 out of 7 rmAbs displayed an increased reactivity towards cit-CRT. Controls mAbs showed no reactivity towards FLS and CRT. Conclusions: Here, we provided evidence that locally differentiated B cells within RA synovial germinal center-like structures can react towards native/cit-CRT likely expressed in RA-FLS. Importantly, this reactivity was disease-specific. The identification of additional cit-antigens such as cit-CRT may provide further insight into the RA pathogenesis. Thus, they might be used as potential new biomarkers in RA diagnosis. References: I McInnes and G Schett. N Engl J Med, 2011. M Sorice, et al. Rheumatology, 2016. K Dasuri, et al. Arthritis Res Ther, 2004. J Holoshitz, et al. Ann N Y Acad Sci, 2010. M Ni, et al. J Clin Immunol, 2013. E Corsiero, et al. Ann Rheum Disease, 2015.